ANALISIS KUALITAS BUTIR SOAL AKUNTANSI DAN PERBANKAN DASAR MENGGUNAKAN APLIKASI ANATES - Dinda Putri Romiyanti; Luqman Hakim; Vivi Pratiwi; Rahma Nur Indana; Livia Dhea Intan Nuraini; Yahya Ahmad Fatahillah; Tya Rahma Sari; Atika Mutiara Noer Kamari; Aurel Feysa Resnandya (STKIP Subang, 2025)
This study aims to analyze the quality of test items developed by Accounting Education students at Universitas Negeri Surabaya for the topic of Principles and Concepts of Accounting and Basic Banking. The analysis was conducted using the Anates application to evaluate item validity, reliability, difficulty level, discrimination power, and distractor effectiveness. Twenty respondents, consisting of vocational students and undergraduate accounting education students, completed a set of 63 multiple-choice items. The results show that the test has a high reliability coefficient, indicating strong internal consistency. However, many items were categorized as very easy, had low discrimination power, or contained ineffective distractors, suggesting the need for revision. Only about half of the items met acceptable validity criteria. These findings emphasize the importance of empirical item analysis in producing accurate and fair evaluation instruments, and highlight the necessity of improving pre-service teachers’ competence in test development and psychometric assessment.